Glucose transporters are abundant in cells with "occluding" junctions at the blood-eye barriers. - Harik, S I (1990)
We studied the distribution of the "erythroid/brain" glucose transporter protein in the human and rat eye by immunocytochemistry with monoclonal and polyclonal antibodies to the C terminus of the human erythrocyte glucose transporter. We found intense immunocytochemical staining in the endothelium of microvessels of the retina, optic nerve, and iris but not in microvessels of the choroid, ciliary body, sclera, and other retro-orbital tissues. In addition, we found marked immunocytochemical staining of retinal pigment epithelium, ciliary body epithelium, and posterior epithelium of the iris. The common feature of all those endothelial and epithelial cells that stained intensely for the glucose transporter is the presence of "occluding" intercellular junctions, which constitute the anatomical bases of the blood-eye barriers. We propose that a high density of the glucose transporter is a biochemical concomitant of epithelial and endothelial cells with barrier characteristics, at least in tissues that have a high metabolic requirement for glucose.